2021
DOI: 10.1186/s12894-021-00897-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the prostate health index in predicting the presence and aggressiveness of prostate cancer among Korean men: a prospective observational study

Abstract: Background We aimed to evaluate the usefulness of the Beckman Coulter prostate health index (PHI) and to compare it with total prostate-specific antigen (PSA) levels and related derivatives in predicting the presence and aggressiveness of prostate cancer (PCa) in the Korean population. Methods A total of 140 men who underwent their first prostate biopsy for suspected PCa were included in this prospective observational study. The diagnostic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The Beckman Coulter Prostate Health Index (PHI) gives a more accurate result, further rules out false-positive test results for men with high PSA levels, and provides a better understanding of the aggressiveness of the disease. [20][21][22] However, it is validated only within total PSA levels ranging from 4 to 10 ng/ml; this is a major downside because three fourths of men with PSA levels within this range may not have prostate cancer. 23 Although PSA has been the gold standard for detecting prostate cancer, its shortcoming lies in its high sensitivity and very low specificity.…”
Section: Dilemma Of Prostate Cancer Screening For Early Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Beckman Coulter Prostate Health Index (PHI) gives a more accurate result, further rules out false-positive test results for men with high PSA levels, and provides a better understanding of the aggressiveness of the disease. [20][21][22] However, it is validated only within total PSA levels ranging from 4 to 10 ng/ml; this is a major downside because three fourths of men with PSA levels within this range may not have prostate cancer. 23 Although PSA has been the gold standard for detecting prostate cancer, its shortcoming lies in its high sensitivity and very low specificity.…”
Section: Dilemma Of Prostate Cancer Screening For Early Detectionmentioning
confidence: 99%
“…34,35 More recent studies in China and Korea have suggested possible health economic benefits of adopting the PHI test for prostate cancer screening. 20,36 However, there is skepticism over its use in the United Kingdom. 37,38 This could be mainly due to inadequate research into its applicability in the UK population.…”
Section: Current State Of Prostate Cancer Screening In the United Kin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The AUC for PHI in the overall group was 0.76 (which was higher than tPSA, fPSA, %fPSA) and in the sub-group with GS ≥ 7, a value of 0.87 was obtained. PHI was a strong independent prognosticator of PCa particularly for the presence and aggressiveness (GS ≥ 7) of the disease, and its application could prevent a substantial amount of unnecessary prostate biopsies [77]. Furthermore, there are other recent studies that have demonstrated that PHI is more specific than tPSA in PCa detection [78] and a better predictor than %fPSA in detecting PCa at prostate biopsy [79].…”
Section: Prostate Health Indexmentioning
confidence: 99%
“…The isoform [-2]proPSA (p2PSA), which is a truncated variant of proPSA, is a relatively new serum marker for the early diagnosis of PCa (7). P2PSA derivatives, percentage of p2PSA (%p2PSA) and prostate health index (PHI), are calculated based on p2PSA and are superior to free PSA (fPSA) in diagnosing and predicting PCa (8,9).…”
Section: Introductionmentioning
confidence: 99%